Apuntes sobre el cálculo de umbrales de notificación en el control de concentraciones empresariales - Felices Saavedra, Enrique (2021)
In this paper, the authors analyze the notification thresholds in merger control based on a conceptual and practical perspective. This, considering its treatment in doctrine, comparative law and guidelines from different countries and institutions in order to present a complete and grounded vision on the subject